Analisis Program Tayangan TVRI dan RRI Sumut Menjelang Pilpres dan Pileg 2024 - Patralihan, Hotmatua; Zein, Silvia Anggraini; Zahara, Cantika; Ahmad, Fitri Nur; Anasya, Anasya; Fauziah, Ade Anggelina (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2024)
This research discusses the analysis of North Sumatra TVRI and RRI broadcast programs ahead of the 2024 presidential and legislative elections. The elections will be held on February 14 2024. The event will be held to elect the President, Vice President, members of the DPR, Provincial DPRD, Regency/City DPRD, members DPD, as well as regional head elections (Governor, Regent, Mayor). The research method used is a qualitative method using desk study and field study techniques, that is, research using the method of collecting data from information as well as carrying out analysis and re-examining secondary data. The results of research by TVRI and RRI have created many programs ahead of the 2024 elections, both at the central and regional levels. Presenting news with the theme